Looking into EFL Students’ Intercultural Awareness and Its Relation with Varying Social Media Exposure and Reading Ability - Erlangga, Fajar; Anam, Syafi’ul (IJLECR (International Journal of Language Education and Cultural Review), 2024)
With explosive growth of technology and globalization, seeing vastly different culture has become part of our daily life as seen in social media. Students’ social media exposure is closely related to their reading activity. Thus, great reading ability leads to great intercultural awareness. This study aimed to investigate EFL students’ intercultural awareness and its relation with varying social media exposure and reading ability. The quantitative study employed ex-post-facto design, with participation of 183 EFL students purposively recruited from Informatics Study Program in a private univerisity in Jakarta, Indonesia. The data collected using online questionnaires and reading tests were analyzed using SPSS 27. With this software, descriptive statistics were made to compare means, percentages, and standard deviations of students’ intercultural awareness. Paired-samples t-tests were run to find out a significant difference in participants’ intercultural awareness by varying social media use and reading ability. The results revealed EFL students’ high intercultural awareness with no significant difference found in students’ varying social media use and with a significant difference found in students’s varying reading ability. In conclusion, EFL students’ intercultural awareness is influenced significantly by their reading abilities rather than their social media exposure.